34z=-18

Multiply both sides of the equation by 43.

43⋅34⋅z=43⋅-18

Simplify 43⋅34⋅z.

Cancel the common factor of 4.

Cancel the common factor.

43⋅34⋅z=43⋅-18

Rewrite the expression.

13⋅3⋅z=43⋅-18

13⋅3⋅z=43⋅-18

Cancel the common factor of 3.

Cancel the common factor.

13⋅3⋅z=43⋅-18

Rewrite the expression.

1⋅z=43⋅-18

1⋅z=43⋅-18

Multiply z by 1.

z=43⋅-18

z=43⋅-18

Simplify 43⋅-18.

Cancel the common factor of 3.

Factor 3 out of -18.

z=43⋅(3(-6))

Cancel the common factor.

z=43⋅(3⋅-6)

Rewrite the expression.

z=4⋅-6

z=4⋅-6

Multiply 4 by -6.

z=-24

z=-24

z=-24

Solve for z 3/4z=-18